Jersey and Holstein cow selection during lactation according to phenotypic characteristics: production and reproduction (UNED Research Journal, 2019)
Introduction: associating the physical characteristics of the animals within a production system is a tool to group animals that can adapt to climate, topography, and handling conditions, without an impact on their productivity. Objective: our objective was to evaluate the relationship between 17 physical variables, from 1 260 animals of the Holstein and Jersey breeds, with their productivity in milk production systems located on the foothills of the Poás Volcano in Alajuela, Costa Rica, during the years 2013 and 2014. Methods: the nutritional and sanitary conditions of the studied farms were very similar. To this end we reconciled information of the daily production per cow, the lactation production adjusted to 305 days, the interval between calves, open days, postpartum days to the first service, and services for conception. Results: the height, physical capability, characteristics of the milk, strength, and rump angle are the parts of the cow that have the most influence on their reproductive performance. The conformation of the udder has no influence on the reproduction parameters, there are no statistical differences between the different scores for the characteristics of the udder and the reproductive parameters, but some trends of both breeds can be mentioned. The udder is more related to milk production than the legs and the hooves. Conclusions: the results of this research are exploratory, but they highlight variables that help define a voluntary selection program of Holstein or Jersey animals during the lactation period, which will help obtain animals that can adapt to the handling, environmental, nutritional, and sanitary characteristics of each system.
Keywords: milk production; lineal measuring; calving interval; dairy character; udder; hooves